2011
DOI: 10.3354/meps09187
|View full text |Cite
|
Sign up to set email alerts
|

Cannibalism among size classes of larvae may be a substantial mortality component in tuna

Abstract: Cannibalism among size classes may reduce starvation and improve survival of larval tuna in oligotrophic ocean areas, but it may also be a substantial mortality component depending on the availability of alternative prey. Here, we combine laboratory and field data on tuna larvae with a model of larval foraging and bioenergetics to explore the role of cannibalism in cohort development at different temperatures, durations of hatching period, hatching larval densities and natural mortality rates. Prey fields (zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 53 publications
5
26
0
Order By: Relevance
“…Reglero et al, ; Llopiz, ). It is possible that an early switch to piscivory is connected to water temperature, as higher temperatures tend to promote a higher frequency of piscivory (Reglero et al, ). This was corroborated by Llopiz (), who found that piscivory in the early development of fish was most frequent at lower latitudes, but a mechanistic understanding of how water temperature influences the size‐related timing of ontogenetic switches to piscivory is missing.…”
Section: The Nature Of Odssmentioning
confidence: 99%
“…Reglero et al, ; Llopiz, ). It is possible that an early switch to piscivory is connected to water temperature, as higher temperatures tend to promote a higher frequency of piscivory (Reglero et al, ). This was corroborated by Llopiz (), who found that piscivory in the early development of fish was most frequent at lower latitudes, but a mechanistic understanding of how water temperature influences the size‐related timing of ontogenetic switches to piscivory is missing.…”
Section: The Nature Of Odssmentioning
confidence: 99%
“…5 E-mail: viktor.j.nilsson@gmail.com intruders (Oyugi et al 2012). Finally, cannibalism, the consumption of conspecifics, and intraguild predation, the killing and consumption of potential competitors, have also been shown to be temperature dependent (Crumrine 2010, Reglero et al 2011. Because these interactions occur between individuals that compete for a shared resource, we will refer to them collectively as competitive interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is generally thought that cannibalism may be one of the main sources of feeding success at early life stages of bluefin (Reglero et al 2011(Reglero et al , 2014, stomach content analysis has not been able to verify piscivory in field-captured ABFT larvae (Catalan et al 2011). By contrast, piscivory in ABFT larvae has been observed in the Gulf of Mexico (Llopiz et al 2010(Llopiz et al , 2014.…”
Section: Introductionmentioning
confidence: 99%